The American image ; Photographs from the National Archives, 1860-1960 - 20160731 frey50; General Services Administration (Pantheon Books New York, 1979)
"The American Image" presents for the first time a selection that shows the range and wealth of the photographic holding of the National Archives in Washington. While the Archives has been used extensively by photographic researchers and historians, this is the first time a book has been based on the whole collection, covering facets of American life over the last hundred years or so.
With an introduction by Alan Trachtenberg.
Keywords: Office of Educational Programs, National Archives and Records Service, GSA; United States - History - 1865- - Pictorial works - Catalogs; United States - History - Photograph collections; United States - History - Pictoiral works